PERANCANGAN APLIKASI PEMBELAJARAN BERBASIS MULTIMEDIA UNTUK ANAK USIA DINI - Halidah, Israini (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
In the widespread research study usingthe Computer Assisted Instruction (CAI) will bemore effective than other tools. Where informationtechnology has an important role in human activity.Can be seen from the awareness of the role ofinformation technology is increasingly widespread in a variety of human activities to the whole societyas well as in education. But at this time of learningfor the children yet to be implemented in earlychildhood early childhood in West Kalimantan arestill manual is with other people who are calledintermediary or intermediaries teaching writingand drawing in the book so that the learningprocess is sometimes very tedious and inefficient.According to a survey conducted in 30 children andthe active role of the parents who accompany therespondents said that children are more likely to behappy playing than learning. Thus the design of theprogram was made based multimedia learningapplication for early childhood in order to assist infacilitating the delivery of learning while playingcompared to oral delivery tailored to aspects thatexist in the CAI. Where CAI are also manydifferent forms dependent skill learning designersand developers, can be shaped the game (games),teach abstract concepts are then dikonkritkan in theform of audio-visual and animated. Once thesoftware design is complete then tested by themethod of User Acceptance Test (UAT). The testresults have shown that the learning program canbe used as an alternative in understanding learningeducation.